‘Here the Refrigerator is Empty’: Food Insecurity among Puerto Rican Elders - Pérez-Velázquez, Carmen M.; Rodríguez-Madera, Sheilla L.; Sánchez-Salgado, Carmen D.; Bernardy-Aponte, Olga I.; Frongillo, Edward A. (Puerto Rico Health Sciences Journal, 2025)
Objective: The authors documented, described, and explained the food insecurity experiences of Puerto Rican elders, particularly how they perceive and give meaning to this phenomenon. Methods: The food insecurity experiences of 50 Puerto Rican elders (≥65 years) were collected using a mixed-methods approach. Qualitative data were collected through in-depth interviews, and quantitative data were obtained from a 22-item questionnaire. The data were integrated with a convergent design. Results: 92% of the participants were food insecure. Puerto Rican elders’ food insecurity experiences have four components (quantity, quality, social, and psychological) and a common pattern of fourteen manifestations. Conclusion: Food insecurity in Puerto Rican elders has causes that go beyond the economic access to food. Addressing food insecurity should be a priority of integrated national food and nutrition policies to reduce the nutritional health inequities among this population. This study presents the first in-depth examination of food insecurity among Puerto Rican elders residing in Puerto Rico, focusing on their cultural interpretations of the phenomenon.